Oud neg.nr. 30 i. 'Een wisselbiljet van de Nationale Roemeense bank'. (Traveler Cheque) - Haas, Joh. de, (1939)
Oud neg.nr. 30 i. 'Een wisselbiljet van de Nationale Roemeense bank'. (Traveler Cheque).